Paulophyton from the carboniferous of Paracas, Peru: a rare but widespread fossil plant with unusual morphology - Iannuzzi, R (2015)
We thank the leadership of the Reserva National de Paracas, the Institute Nacional de Recursos Naturales, and the Ministerio de Ambiente for permissions and support during our research at the Paracas site. We acknowledge partial support for this research by CONCYTEC to V.A., the National Science Foundation (EAR-8916826), and the University of Pennsylvania Research Foundation to H.W.P., and CAPES (Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior, Process no. BEX 0461/03-2) and CNPq (Conselho Nacional de Pesquisa, Process no. PQ 309211/2013-1) to R.I. Also, we would like to thank the reviewers H.A. Carrizo and R. Rohn for their fruitful suggestions. R. Jones helped with the photography and D. Wang and B. Trenk assisted with the rendition of figures.